(untitled) (Research, Society and Development, 2021)
Objective: To describe the occupation of ICU beds dedicated to COVID-19 in the period close to Carnival and the measures taken to contain the virus in the state of Goiás. Methodology: This is a retrospective, observational and descriptive study. Occupancy rates of ICU beds destined to COVID-19 were used, by region in the state of Goiás, taken from the risk maps of March 17, 27 and 5, 2021; in addition to decrees and norms from February 11 to June 2021, taken from the SES-GO Portal and the Civil House of Goiás. Results and discussion: The average ICU bed occupancy rates increased about 12% after Carnival. March was considered by the media as the worst month of the pandemic so far, due to the P1 variant. Among the virus containment measures, decrees and norms were issued, but the growing distribution and application of vaccines is highlighted, which brought a more favorable scenario in June. Conclusion: During the period close to Carnival, ICU bed occupancy rates increased in Goiás. Among the measures, there was physical distance, relocation of beds, hand hygiene, the use of masks and vaccination.